The effect of therapy on subclinical atherosclerosis of the carotid arteries in patients with calcium pyrophosphate crystal deposition disease and osteoarthritis (pilot study) - M. S. Eliseev; O. V. Zhelyabina; M. N. Chikina; E. I. Markelova; I. G. Kirillova; Yu. O. Korsakova; A. A. Kobriseva (Научно-практическая ревматология, 2021)
Endothelial dysfunction associated with chronic microcrystalline inflammation plays a role in the progression of atherosclerosis in calcium pyrophosphate crystal deposition diseases (CPPD).The aim of the study was to assess the dynamics of the development of atherosclerosis based on changes in the thickness of the intima-media complex (ICIM) of the carotid arteries (CA) in patients with CPPD receiving long-term anti-inflammatory therapy (colchicine, methotrexate, hydroxychloroquine).Materials and methods. 26 patients with CPPD and 26 patients with osteoarthritis aged over 18 years old were included. Exclusion criteria: age >65 years; presence of cardiovascular diseases. The blood lipid spectrum, hs-CRP level, anthropometric parameters were determined for all, and Doppler ultrasound ultrasonography of the carotid arteries (CA) was performed. Patients were followed up for not <6 months, assessed ICIM CA at 1 visit, then patients with CPPD, at the discretion of the attending physician, were prescribed methotrexate at a dose of 15 mg per week, hydroxychloroquine 200 mg 1 time per day or colchicine 0.5 mg 2 times a day. Patients could take NSAIDs if they were in pain. The SCORE index has been calculated for everyone.Results. Initially, ICIM values did not differ in patients with CPPD and OA. Initially, ICIM>0.9 mm were detected in 11 of 22 (50%) patients with CPPD and in OA in 8 of 19 (42%) (p=0.39). In dynamics, patients with CPPD revealed a decrease in the number of patients with ICIM>0.9 mm from 42 to 18%. At the same time, in 8 patients with CPPD, ICIM>0.9 mm was combined with a CRP level >0.2 mg/l. Out of 22 patients with CPPD, 14 (64%) patients showed a decrease in the mean values of ICIM, in 2 (9%) patients - an increase, in 5 patients the mean values of ICIM did not change. After 6 months of therapy, out of 11 patients with CPPD with ICIM >0.9 mm, after 6 months of therapy, in 7 cases there was a decrease in the indicator less than the specified value, in 5 of them a decrease in serum CRP level <2 mg/l was recorded. In patients with CPPD, the serum CRP level significantly decreased; in patients with OA, it did not change. Out of 19 patients with OA, 9 (47%) patients showed an increase in the mean ICIM over time, while the rest did not change. In those treated with hydroxychloroquine, a decrease in the mean ICIM parameters was observed in 5 out of 6 (83%) patients, colchicine - in 6 out of 9 (67%) patients, methotrexate - in 4 out of 7 (57%) patients.With CPPD, the result of therapy with colchicine, methotrexate and hydroxychloroquine in relation to the development of the initial signs of atherosclerosis according to Doppler ultrasound ultrasonography of CA can be realized based on the presence of chronic inflammation.